Changes in exercise characteristics, maximal voluntary contraction, and explosive strength during prolonged tennis playing - Girard, O.; Lattier, G.; Micallef, J. P.; Millet, G. P. (British Journal of Sports Medicine, 2006)
Objectives: To examine changes in exercise characteristics, maximal voluntary contraction, and explosive strength during prolonged tennis playing.